Abrupt changes in the graphene on Ge(001) system at the onset of surface melting. (April 2019) - Persichetti, L.; Di Gaspare, L.; Fabbri, F.; Scaparro, A.M.; Notargiacomo, A.; Sgarlata, A.; Fanfoni, M.; Miseikis, V.; Coletti, C.; De Seta, M.
Abstract: By combining scanning probe microscopy with Raman and x-ray photoelectron spectroscopies, we investigate the evolution of CVD-grown graphene/Ge(001) as a function of the deposition temperature in close proximity to the Ge melting point, highlighting an abrupt change of the graphene's quality, morphology, electronic properties and growth mode at 930 °C. We attribute this discontinuity to the incomplete surface melting of the Ge substrate and show how incomplete melting explains a variety of diverse and long-debated peculiar features of the graphene/Ge(001), including the characteristic nanostructuring of the Ge substrate induced by graphene overgrowth. We find that the quasi-liquid Ge layer formed close to 930 °C is fundamental to obtain high-quality graphene, while a temperature decrease of 10° already results in a wrinkled and defective graphene film. Graphical abstract: Image 10889687